2015
DOI: 10.1007/s11948-015-9690-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Social Justice into Traffic Control for Self-Driving Vehicles?

Abstract: The convergence of computing, sensing, and communication technology will soon permit large-scale deployment of self-driving vehicles. This will in turn permit a radical transformation of traffic control technology. This paper makes a case for the importance of addressing questions of social justice in this transformation, and sketches a preliminary framework for doing so. We explain how new forms of traffic control technology have potential implications for several dimensions of social justice, including safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 63 publications
0
28
0
1
Order By: Relevance
“…They found that the combined increase in travel demand from different social groups could result in a 14% increase in annual light-duty VMT for the US population. Finally, Mladenovic and McPherson (2016) analyzed the opportunities arising from vehicle automation to incorporate social justice in future traffic control systems in terms of efficiency and equal access.…”
Section: Assumptionsmentioning
confidence: 99%
“…They found that the combined increase in travel demand from different social groups could result in a 14% increase in annual light-duty VMT for the US population. Finally, Mladenovic and McPherson (2016) analyzed the opportunities arising from vehicle automation to incorporate social justice in future traffic control systems in terms of efficiency and equal access.…”
Section: Assumptionsmentioning
confidence: 99%
“…That is, AVs decision-making, will be previously introduced by someone, "many or all of those decisions will have to be programmed into the car," (Ong, 2017:p.36), therefore, we have the fundamental role of the engineering department, responsible for programming AVs and, consequently, its dissemination. Mladenovic and McPherson (2016) says that decision-making power should not be concentrated solely in a small group of experts, especially if financial interests have exclusive influence. This group should not have exclusive rights to decide on all the moral aspects of these machines behavior (Martin, 2016).…”
Section: Ethics/moral/liabilitymentioning
confidence: 99%
“…Finally, we cannot eliminate the need for a public and democratic discussion of relevant societal values that technology shapes. As a result, it is necessary to engage in a transparent manner all relevant corporate groups in critical discussions and decision-making (Mladenovic & McPherson, 2016). Change is inescapable and not necessarily a bad thing in itself.…”
Section: Ethics/moral/liabilitymentioning
confidence: 99%
“…Social justice relates to the distribution of wealth and privileges in society, as well as issues related to poverty and development. There are a growing number of advocates that engineering social responsibility encompasses social justice issues, including engineering faculty in the US [64,65], Australia [66], Finland [67], and Colombia [68]. A group devoted to this issue, Engineering, Social Justice, and Peace (ESJP), routinely hosts a conference.…”
Section: Social Justicementioning
confidence: 99%